A Novel Prognostic Marker and Therapeutic Target Associated with Glioma Progression in a Tumor Immune Microenvironment - Zhang JJ; Zhang Y; Chen Q; Chen QN; Yang X; Zhu XL; Hao CY; Duan HB (Dove Medical Press, 2023)
Jun-Jie Zhang,1,* Yu Zhang,2,* Qian Chen,1 Qi-Ning Chen,1 Xin Yang,1 Xiao-Lin Zhu,1 Chun-Yan Hao,3 Hu-Bin Duan1 1Department of Neurosurgery, First Hospital of Shanxi Medical University, Taiyuan, Shanxi, 030001, People's Republic of China; 2Department of Neurosurgery, Beijing Tiantan Hospital, Capital Medical University, Beijing, People's Republic of China; 3Department of Geriatrics, First Hospital of Shanxi Medical University, Taiyuan, Shanxi, 030001, People's Republic of China*These authors contributed equally to this workCorrespondence: Hu-Bin Duan; Chun-Yan Hao, Tel +8613994201664 ; +8613803494928, Email hubinduan68@163.com; haochunyan68@126.comBackground: Immune microenvironment serves a vital role in glioma progression, and a large number of studies have found that tumor progression can be reduced to some extent by modulating the immune process in tumors.Materials and Methods: ImmuneScore of each sample in CGGA datasets were calculated with Estimate R package, and samples were grouped by median ImmuneScore values for differential analysis to obtain immune microenvironment differential genes. We further conducted survival analysis, ROC curve analysis, independent prognostic analysis, and clinical correlation analysis on glioma sample genes in CGGA to obtain glioma prognostic genes, and then identified their intersection with immune microenvironment DEGs by Venn tool. The GEPIA and UALCAN databases were used to verify the differential expression of intersecting genes in the glioma and normal brain and to identify our target gene. After validation of their prognostic value, we constructed a nomogram to calculate the risk score and to estimate the accuracy of prognostic model. We mined co-expression genes, enriched functions and pathways, and correlations to immune cell infiltration of unigene with an online database. Finally, we verified the differential expression of FCGBP in glioma by immunohistochemical staining.Results: We finally selected Fc fragment of IgG-binding protein (FCGBP) as our study gene. The prognostic values of FCGBP were validated by a series of analyses. Immunohistochemical staining showed that FCGBP expression increased in gliomas and was up-regulated with the progression of glioma grade.Conclusion: As a key unigene in glioma progression, FCGBP contributes to the regulation of immune microenvironment and has the potential to be a prognostic biomarker and immune targets.Keywords: glioma, immune microenvironment, FCGBP, tumor progression, therapeutic target